Innovation in the Enforcement of Child Support Orders after Divorce in Interfaith Marriages: a Comparative Study of Indonesia and Malaysia - Yustri, Ermida; Ikromi, Zul; Erwan, Edi (Islam Transformatif : Journal of Islamic Studies, 2025)
Divorce in interfaith marriages presents distinct challenges in the enforcement of child maintenance orders, particularly when religious differences between parents affect the rights of the child after divorce. In Indonesia and Malaysia, differences in legal systems and regulations governing post-divorce child maintenance have given rise to different forms of legal innovation in the enforcement of such rulings. In Indonesia, the main challenge lies in the dualism of the judicial system, which separates religious courts from civil courts. Meanwhile, Malaysia, despite its pluralistic legal framework, faces problems mainly in cases where the child is Muslim while the father is non-Muslim. This article offers a comparative analysis of the two countries in terms of legal innovation and the enforcement of child maintenance orders following divorce in interfaith marriages, with a particular focus on the role and practice of the Bahagian Sokongan Keluarga (BSK) in Malaysia. Through a comparative approach, this study highlights both similarities and differences in legal enforcement mechanisms and provides recommendations to enhance the protection of children’s rights in post-divorce child maintenance cases. This study finds that the fulfillment of child maintenance obligations in interfaith divorce cases, especially when the child is Muslim and the father is non-Muslim, presents complex legal issues. In Indonesia, the absence of a specialized institution similar to BSK results in enforcement of child support relying heavily on litigation processes, which are often hindered by jurisdictional and administrative limitations. Meanwhile, Malaysia, through BSK, has introduced administrative innovations, including mediation mechanisms and inter-agency coordination, which have accelerated the efficiency of child support fulfillment. Therefore, this recommends the establishment of a similar institutional unit in Indonesia, the harmonization of civil and Syariah data, and the development of standarized national operating procedures (SOPs) as reform efforts to better guarantee children’s rights in interfaith marriages cases.